A new species of Mimosa sect. Mimosa (Leguminosae, Mimosoideae) from Southern Brazil - Morales, Matias; Santos-Silva, Juliana; Ribas, Osmar S. (Springer, 2019)
A new species of Mimosa section Mimosa, Mimosa eurystegia, which is apparently endemic to Paraná in southern Brazil, is described and illustrated. This species is distinguished by plurinerved leaflets and papyraceous, plurinerved, orbicular, amplexicaul stipules. Morphological distinctiveness of this new Mimosa and its relationships with allied species are discussed. Phenological, geographical and ecological data are presented, in addition to a key to the species of Mimosa subser. Sparsae.